2018
DOI: 10.1051/epjn/2018028
|View full text |Cite
|
Sign up to set email alerts
|

Checking, processing and verification of nuclear data covariances

Abstract: The aim of this paper is to present the activities carried out by NEA Data Bank on checking, processing and verification of JEFF-3.3T4 covariances. A picture of the completeness and status of the JEFF-3.3T4 covariances is addressed. The verification of JEFF-3.3T4 covariances is performed with nuclear data sensitivity tool providing the keff uncertainty as a function of the contributing nuclide-reaction pairings including cross-reaction covariances. A total number of 4501 ICSBEP benchmarks is used in this analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…3. The covariances were converted with NJOY into the BOXER format, a format recognised by the well-known NEA visualization tool JANIS and by sensitivity codes such as NDaST [419].…”
Section: Processing Covariance Datamentioning
confidence: 99%
See 2 more Smart Citations
“…3. The covariances were converted with NJOY into the BOXER format, a format recognised by the well-known NEA visualization tool JANIS and by sensitivity codes such as NDaST [419].…”
Section: Processing Covariance Datamentioning
confidence: 99%
“…Finally, it was found that the group structure of covariance data is also important, as can be seen from the results of the intermediate spectrum benchmarks, where a coarse group structure used to represent the covariance data of 239 Pu in the JEFF-3.3 library leads to higher uncertainty estimates. Table 52 gives the average uncertainty contributions in pcm in k eff calculated with the NDaST [419,424] tool for 4519 cases from the ICSBEP Handbook [23] with the precalculated sensitivities available in DICE [425]. Results are averaged by fissile material and spectrum and compared with the average experimental uncertainty.…”
Section: Criticalitymentioning
confidence: 99%
See 1 more Smart Citation
“…7). This agreement can be observed for the rest of relevant isotopes/reactions but a more extensive analysis would be worthwhile following the methodology proposed in [13]. This would allow to test in a more comprehensive way.…”
Section: Processing and Testing Coverx Jeff-33 Covariancesmentioning
confidence: 56%